Implemention of system landslide disaster mitigation based internet of things - Tua, Rendi Sahila; Muthalib, Muchlis Abdul (Geuthèë Institute, 2024)
Landslide mitigation tools are specifically made to detect angular slopes in the ground. This tool is a series of simple tools that utilizes an ESP32 microcontroller and real-time monitoring media via smartphone. This landslide mitigation tool consists of a tool frame which is generally made of iron, a mpu6050 sensor and a controller box. The main power source for the tool comes from a battery with a capacity of 12 V 7A. This tool is equipped with other components such as LCD, MPU6050 sensor, relay and siren. The designed tool will be placed in areas where landslides often occur. The MPU6050 sensor plays a role in detecting slopes on the ground. When the sensor detects a predetermined tilt level, the sensor will send data to the microcontroller. The microcontroller will process the data and send notifications to the smartphone via the blynk application. Along with this, data will also be displayed on the LCD and the sirens will be active to provide an indication that a landslide will occur. Based on testing, the average notification display delay on the LCD is very small, namely 0.26s, while the average notification delay on smartphones via the blynk application is 0.30s. The percentage measurement error by the MPU6050 sensor is 1.2%.